Deconstruction And Simulacra: A Postmodern Critique Of Management Science - Muhammad Ilham Alimuddin; Muhammad Yunus Amar (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
This study analyzes management science and organizational practice through the lens of postmodernism, employing Derrida's deconstruction and Baudrillard's theory of simulacra to unpack the discursive structures and representational functions within contemporary management. Situated within the framework of Critical Management Studies (CMS), this research addresses the risk of stagnation and "formulaic radicalism" in contemporary critical scholarship, highlighting the need for more specific and nuanced analytical approaches. Consequently, the study aims to apply postmodern conceptual tools to deconstruct managerial discourse and practices. The proposed methodology is a qualitative-theoretical analysis, utilizing Jacques Derrida's deconstruction to dismantle internal logical structures and Jean Baudrillard's theory of simulacra to analyze external representational functions. The deconstructive analysis reveals that central concepts, such as leadership, are constructed upon unstable and hierarchical binary oppositions (e.g., Leader/Follower). Concurrently, the analysis of simulacra demonstrates that practices like Corporate Social Responsibility (CSR) often function as pure simulacra within a managerial hyperreality, where image supersedes substance. A synthesis of these findings suggests that managerial discourse is not a neutral reflection of reality but a productive force that actively constructs reality to serve specific power relations. This study contributes to CMS by offering a more nuanced postmodern analytical model. It also positions critique as a Foucauldian intervention, opening possibilities for more ethical, reflective, and emancipatory management practices.